Mesopore Development in Activated Carbon Fibres by Additional Chemical Activation - Song Lei; Junichi Miyamoto; Hirofumi Kanoh; Katsumi Kaneko (Adsorption Science & Technology)
Mesoporous activated carbon fibres (ACFs) were prepared from pitch-based microporous carbon fibres by additional chemical activation using calcium nitrate [Ca(NO 3 ) 2 ] and disodium hydrogen phosphate (Na 2 HPO 4 ) as activation agents. The porosity change was examined by performing N 2 adsorption measurements at 77 K. The nitrogen adsorption isotherm varied as a result of re-activation with Na 2 HPO 4 or Ca(NO 3 ) 2 at 1123 K or 1173 K for 1 h or 2 h, with that of the re-activated ACFs exhibiting explicit H4 or H1 hysteresis. The use of Ca(NO 3 ) 2 for chemical activation produced more mesopores than Na 2 HPO 4 , the maximum mesopore volume being 0.92 ml/g. The largest volume ratio of mesopores to micropores was greater than three and the surface areas were greater than 1000 m 2 /g.